2010
DOI: 10.1007/s12603-010-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

A one-year follow-up study into the course of depression after stroke

Abstract: Half of PSD patients become depressed within the first month after stroke. Although most patients recover, a clinician has to be aware that symptoms can recur especially in older patients and that in patients with major depression symptoms may be persistent. In these patients treatment should be considered, whereas in patients with limited disease an observational approach may suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 28 publications
(33 reference statements)
4
28
0
2
Order By: Relevance
“…Early-onset PSD was defined as depression diagnosed at 14 ± 2 days. Patients diagnosed at any later follow-ups and did not withdrawn from follow-up before the diagnosis of depression formed late-onset PSD group [17]. Patients who were not diagnosed with depression at any of the four follow-up visits were included in the non-depressed group.…”
Section: Methodsmentioning
confidence: 99%
“…Early-onset PSD was defined as depression diagnosed at 14 ± 2 days. Patients diagnosed at any later follow-ups and did not withdrawn from follow-up before the diagnosis of depression formed late-onset PSD group [17]. Patients who were not diagnosed with depression at any of the four follow-up visits were included in the non-depressed group.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] One possible explanation is the low rate of antidepressant or psychological treatment received by our patients. In line with the literature, the baseline stroke severity and depression severity predicted nonremission of PSD.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study of 138 stroke survivors, nonremission of PSD was associated with more disabling stroke and severe depression. 3 The main limitation of this study was the small sample size and the relatively high attrition of patients for follow-up, which reduced its statistical power. Furthermore, the stroke severity of the final study sample was mild.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies that reported group means in depression questionnaires without distinguishing between subclinical symptoms and depressive disorder were not included. Ten prospective longitudinal studies fulfilled these criteria for PSD [8,9,13,[15][16][17][18][19][20][21] . The rates of patients classified as depressive were pooled and averaged across studies, so that the resulting mean rates were weighted according to the sample size.…”
Section: Review Of Prospective Longitudinal Researchmentioning
confidence: 99%